The distribution of financial well-being and income within the household. - Bonke, J; Browning, M (Springer, 2009)
In this paper, we consider the issue of the intra-household distribution of welfare directly using a survey measure of self-perceived economic well-being. We develop a theoretical model of satisfaction within the household for couples. In the empirical analysis, we find that husbands and wives often report different levels of financial satisfaction. The most important correlate of relative satisfaction within the household is found to be relative income. This is a direct confirmation of the previously implicit findings and is predicted by our theoretical model.